Variation in Bacterial Community Structures and Functions as Indicators of Response to the Restoration of Suaeda salsa: A Case Study of the Restoration in the Beidaihe Coastal Wetland - He, Changfei; Zheng, Li; Ding, Jinfeng; Gao, Wei; Li, Qian; Han, Bin; Li, Jingxi (Frontiers in Microbiology, 2022)
Microbes play an essential ecological role in the restoration of degraded coastal wetlands. However, there are few studies on the ecological role of bacteria in the restoration process. Here, Suaeda salsa (S. salsa) was planted in the degraded area of Beidaihe coastal wetland to recover the biodiversity. We monitored the main soil environmental factors, bacterial community composition, and putative biogeochemical functions in the restoration process. After planting S. salsa, total organic carbon (TOC) significantly increased gradually, and pollutants such as the heavy metal and polycyclic aromatic hydrocarbon (PAH) concentrations decreased in the LPR, suggesting an improvement of soil quality via the growth of S. salsa. Soil bacterial α-diversity increased with restoration and was positively correlated with TOC, indicating a close relationship between soil environmental factors and bacterial diversity. Proteobacteria dominated during the restoration period, although Bacteroidetes, Planctomycetes, Gemmatimonadetes, and Acidobacteria were sensitive to the planting restoration. Random forest analysis identified 30 key OTUs and found that the sum of the relative abundances of key bacterial OTUs was an excellent biological indicator to evaluate wetland health. The β-diversity showed that the growth of S. salsa reshaped the soil bacterial community structure and function in the LPR, which mainly was similar to those in the control area. Putative biogeochemical functions showed that symbionts and aromatic compound degradation were dominant bacterial functions in the growth period of S. salsa (PC, LPC, and LPR), which were positively correlated with the bacterial richness and TOC concentration. Our study proposed new indicators to assess or diagnose the restoration effect or coastal wetland health and found that the restoration of S. salsa increased bacterial taxa with the ability of symbionts and aromatic compound degradation. This study expanded our knowledge of coastal wetland restoration and ecological contributions.